2013
DOI: 10.3310/hta17410
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the growth and rupture rates of small abdominal aortic aneurysms: implications for surveillance intervals and their cost-effectiveness

Abstract: This report should be referenced as follows:Thompson SG, Brown LC, Sweeting MJ, Bown MJ, Kim LG, Glover MJ, et al. Systematic review and meta-analysis of the growth and rupture rates of small abdominal aortic aneurysms: implications for surveillance intervals and their cost-effectiveness. Health Technol Assess 2013;17(41). Health Technology Assessment is indexed in MEDLINE, CINAHL, EMBASE, The Cochrane Library and the ISI Science Citation Index and is assessed for inclusion in the Database of Abstracts of Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
177
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(194 citation statements)
references
References 122 publications
5
177
2
1
Order By: Relevance
“…Addressing CV risk may theoretically impact on AAA growth rates, given the shared pathogenetic mechanisms. However, a paucity of evidence still remains in the factors affecting growth rate of such aneurysms (18). Addressing CV risk factors may potentially impact on AAA growth, and potentially have a larger impact on mortality rates than any prophylactic AAA surgery for this cohort group, but more evidence is definitely required to prove such rationale.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing CV risk may theoretically impact on AAA growth rates, given the shared pathogenetic mechanisms. However, a paucity of evidence still remains in the factors affecting growth rate of such aneurysms (18). Addressing CV risk factors may potentially impact on AAA growth, and potentially have a larger impact on mortality rates than any prophylactic AAA surgery for this cohort group, but more evidence is definitely required to prove such rationale.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81] A number of studies have also explored the costs and outcomes of preoperative surveillance. 82,83 However, less is known about the costs and utilities associated with preoperative assessments and postoperative care. In addition, the existing evidence is primarily from trial settings and patient samples, which may be atypical of those in routine care, collected over a limited follow-up period.…”
Section: Data Inputsmentioning
confidence: 99%
“…15 The variation could not be explained by differences in initial AAA diameter alone. 16 The authors suggested that methodological issues, such as differences in imaging modalities, variation in the plane of measurement, and cursor positioning, likely explained the large heterogeneity. Frequently, important methodological aspects were not reported.…”
mentioning
confidence: 99%